An Investigation In The Theory And Boundaries Of The Firm And Their Possible Application To Public Institutions - Leong, Victor (University of Saint Joseph, 2024)
Industrial organization, theory of the firm and boundaries of the firm are well established fields of study involved in the size, structure and scope of a corporate entity (i.e. firm) to the market. However, a key characteristic of corporate entities is that economic concerns (costs and profit) is the overriding or dominant factor. This paper attempts to apply the above mentioned concepts to organizations such as public institutions where economic concerns are secondary considerations, to seek a more objective analysis on what the structure and scope of such organizations should be
Keywords: Hamiltonian Formulation; Theory of the Firm; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Contributions to the Macao's Social Security Fund: the Arbitrary System - Un, Ka Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

PUBLIC POLICIES AND INFRASTRUCTURE FOR ELECTRIC VEHICLES IN MACAO: LOCAL PERSPECTIVES AND EXPERIENCES - Tai, On Teng (University of Saint Joseph, 2024)
This dissertation explores Macao residents' experiences and perspectives regarding Macao's public policies and infrastructure for electric vehicles. It delves into residents' viewpoints on the effectiveness of electric vehicle policy implementation, the layout and convenience of public facilities such as charging stations and designated parking spaces for electric vehicles, and their actual experiences and feedback while using electric cars. This study is significant because it provides valuable insights into Macao residents' fundamental attitudes and needs toward electric vehicle policies and public facilities. By understanding these perspectives, policymakers can make more informed decisions to optimize electric vehicle policies and improve public facilities, ultimately promoting the healthy development of the electric vehicle market in Macao and facilitating the construction of a green transportation system. In terms of research methods, this study primarily employed questionnaires to collect data from road users in Macao. The questionnaires were designed to gather comprehensive information on their experiences and feedback related to electric vehicle policies, infrastructure, and usage. The findings of this study are intriguing. Firstly, it was discovered that Macao residents have a relatively low awareness of electric vehicle policies, but generally, they believe these policies contribute to environmental protection. Secondly, regarding public facilities, some residents reported issues such as uneven distribution and insufficient number of charging stations, as well as inadequacies in using and managing designated parking spaces for electric vehicles. Additionally, residents provided specific opinions and suggestions regarding the purchase costs of electric vehicles and government subsidy policies. Based on these findings, my conclusion is that there is an urgent need to optimize and improve Macao's electric vehicle policies and public facilities. Policymakers should increase publicity efforts to raise residents' awareness of electric vehicle policies and reasonably plan the layout of charging stations and designated parking spaces for electric vehicles to enhance their convenience and availability. Furthermore, the government could consider providing more subsidies and preferential policies for purchasing electric vehicles to reduce the financial burden on residents. These measures will help promote the further development of the electric vehicle market in Macao and facilitate the construction of a green transportation system
Keywords: Electric vehicles; Green transportation; Macao; Public infrastructure; Public policies; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

IMPLEMENTATION OF SDG 1 IN CAPE VERDE: AN ANALYSIS OF POLICIES AND ACTORS - Pasquinha, Patrick Delgado (University of Saint Joseph, 2024)
In the 21st century, poverty still remains a serious issue for the world, halting development and growth of nations. SDG 1 refers to the first Sustainable Development Goal (SDG) established by United nations. It has as goal to “end poverty in all its forms everywhere”. Cape Verde as an UN member also adopted it and aligned national policies to achieve it. This thesis aimed to analyze the different policies adopted by the government of Cape Verde to implement SDG 1. Moreover, this dissertation will also point out the different actors behind the implementation of SGD 1 in Cabo Verde (both national and international actors), as well as find out their role in alleviating poverty in Cabo Verde, in other words, how they contribute to poverty alleviation in Cabo Verde. Based on a qualitative methodology, using document analysis as method to collect the data and further using thematic analysis to analyze, code and categorize the collected data, the study was able to answer the two research questions: Research question 1: What are the different policies adopted by the government of Cape Verde to implement SDG 1. Research question 2: Who and what are the roles of the actors involved in the implementation of SDG 1 in Cape Verde? The findings of the study revealed that: As to research question 1, the study found out that the government of Cape Verde has adopted several policies geared towards poverty reduction. Such policies included social protection policies, investment in infrastructure policies, investment in education policies, investment in health policies, investment in rural development policies, economic diversification policies, gender equality and women empowerment policies, job creation policies and climate change adaptation policies. As for research question 2, the study 4 revealed there are two main Actors are responsible for the implementation of SDG 1, government institutions and National and International Partners. On one hand, the government of Cape Verde is focused on creating and adopting polices that target the poor, as result this make sure that they can lift from poverty or at least avoid they sinking into deeper poverty. On the other hand, the partners (here known as Actors) helping on the implementation of SDG 1 in Cape Verde work as a backup for the government, helping it on other issues related to SDG 1 implementation such as knowledge and capital provision and so on. The Cape Verde government is dedicated to reducing poverty, focusing on the unemployment and migration phenomenon. These factors contribute to poverty and exacerbate it. Despite these challenges, the overall outlook on poverty reduction in Cape Verde is optimistic, indicating a significant commitment to address the root causes of poverty
Keywords: Actors; Cape Verde; Multidimensional poverty; Poverty reduction policies; SDG 1 implementation; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Impact of green finance on Asian economic development - Wong, Kuan Lam (University of Saint Joseph, 2024)
The development of green financial products like green bonds and industry financing has gained momentum, showing positive impacts on sustainable economic development, renewable energy investment, and greenhouse gas emission reduction. As the research problem is inadequately explored, this dissertation aims to fill the research gap to evaluate the impacts of green finance on economic development. Furthermore, this study assesses the differences between Asian and non-Asian economies in the impacts of green finance on economic development. Two empirical measures are analyzed in this study.Green finance is measured with the Global Green Finance Index (GGFI), a composite index that captures over 100 instrumental variables, covering the business environment, human capital, infrastructure, and sustainability aspects of a financial center. Growth rate of gross domestic product (GDP) per capita reflects economic development. The dataset encompasses 83 international financial centers from 2018 to 2022. The regression model finds a significant negative relationship between growth rates of GGFI and GDP per capita in the full sample, the Asian subgroup, and the non-Asian subgroup. GGFI growth is confirmed to have Granger caused GDP per capita growth, but GDP per capita growth did not Granger cause GGFI growth. Combined with the insights of the previous studies, this study justifies the findings as a short-term negative impact of green finance on economic growth. However, the Asian region, with many emerging economies, could transition faster, so the regression derives a less negative coefficients for Asian financial centers. The policy implication 5 is that continued government support to improve the effectiveness of green finance is necessary for the long-term benefit of green finance to be fully realized
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Comparative study: The Human rights situation in China, the USA and Europe - Chu, Pok Tou; Lao-Phillips, Jenny Oliveros (University of Saint Joseph, 2023)
This thesis mainly discusses and compares the human rights situation and the problems in China, the USA and the UK. Also, the thesis will give the solution of how to make the world's human rights situation more fairly. Because we sometimes listen to these countries use cruel ways to suppress the opponents from the news. So I think this will be very suitable for understanding the current human rights situation, problems and movements in these countries. This thesis mainly uses the secondary data analysis method to collect and analyse the data. After analysing the data, three main issues affecting human rights were identified. These issues are race, religion, and network privacy. Other important factors still influence human rights, but this dissertation focused on the three issues identified. Finally, I will give two to three recommendations to practice human rights more fairly. Although the step will be very small, we can greatly improve the fair human rights in the future
Keywords: China; Europe; Human rights; Human rights situation; Thesis and Dissertations Master of Government Studies (MGS); USA; United Kingdom; University of Saint Joseph

STRATEGIES FOR BUILDING A SMART TOURISM CITY: A CASE STUDY OF MACAO SAR AND THE PERCEPTION OF EXPERTS - Da Rosa Ho, Hoi Lam (University of Saint Joseph, 2024)
This dissertation explores the strategies for developing a smart tourism city in the background of Macao Special Administrative Region (SAR) and the perceptions of different experts in Macao. Awared that the Macao government aims to expedite the development of a livable, smart, and green Macao and requires smart technology to be applied to upgrade the people’s livelihood. This is a long-term ambition to achieve and whether success remains uncertain. Through literature review, understood that the traditional tourism industry must be transformed and innovated to enhance competition since the 90s. And smart tourism cities provide enhanced tourists’ experience and residents’ better quality of life. Although prior research have studied the tourist behavior of smart tourism contents or evalutated strategic plans for the construction of a smart tourism city, there is no previous research explored on the topic. Therefore, this dissertation through qualitative research methods including on-site observations, analyzing government-released documents and interviewing relevant experts. The findings present the seven components of the conceptual framework, including physical infrastructures, technology applications, experience sharing, big data, business co-creation, technical professionals, and cyber security, are strongly support the smart tourism city development in Macao. Provide a clear understanding for the relevant stakeholders to practice in a smart tourism city context. In addition, from the perspective of experts, the key for successfully develop Macao as a smart tourism city is that should apply ‘government-led, multi-party participation, and marketing operation’ in every component of the framework. The key for success depends on all stakeholders actively participae the activities. Four recommondations also present at the end of this disseartation. Prospects the development of smart tourism city in Macao can enhance both the quality of tourists’ experience and residents’ life as well as driven the long-term economic growth sustainably
Keywords: Smart Tourism City; Technology and tourism development; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph